Facebook Marketing and its Influence on Consumer Buying Behaviour in Kathmandu - Rana, Arunima (Journal of Business and Social Sciences Research, 2018)
Facebook is one of the leading and rapidly growing online networks. With over 845 million users, Facebook is a very effective place for businesses. There is possibility to attract new customers, build online relationships and use Facebook as an online marketing communication channel. With its highly targeted marketing features and its smooth ability to spread information across the networks of each other, Facebook becomes an important marketing place for marketers these days. Facebook is a convenient medium for customers and prospects to communicate directly to brand representative or about your brand with their friends. However, the question is, which group of people are actually receiving the information and does this information influence their buying behaviour?This paper aims to answer this question based on a study regarding the online activities of 200 Facebook users, by identifying and understanding the consumers buying behaviour varied with different factors like age, gender, occupation, income and how different factors related to Facebook have influenced the respondents’ perception of Facebook marketing in Kathmandu valley. The secondary data comes from several reports, past research, published articles, books, newspaper, website and journals. For clarity purposes, data obtained was reported using simple percentages and frequencies. The study uses mathematical tool, SPSS and Microsoft excel to present the data into quantitative form.Results of the analysis indicates that although marketers spend hours in building brand image, the study found that consumers are less concern about the brand image while making a purchase decision. The findings also reveals that people are more influenced by word of mouth and opinion given by the people they know on Facebook and it substantially affects their buying behaviour. The least effective Facebook marketing factor is celebrity endorsement which implicates that consumers are more affected by views of friends and family rather than endorsement done by celebrities. This calls for more conjunct efforts on the part of companies, ad agencies and advertisers to extend their brand equity and build their customer base. Marketers should adopt relationship marketing strategy and work on bonding with customers for positive impact with better communication and interaction. The targeted customer should be the opinion leaders and social group to facilitate more patronage of the marketed product or service.Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 111-128